2018
DOI: 10.1126/science.aat5671
|View full text |Cite
|
Sign up to set email alerts
|

A liquid phase of synapsin and lipid vesicles

Abstract: Neurotransmitter containing synaptic vesicles (SVs) form tight clusters at synapses. These clusters act as a reservoir from which SVs are drawn for exocytosis during sustained activity. Several components associated with synaptic vesicles likely to help forming such clusters have been reported, including synapsin. Here we found that synapsin can form a distinct liquid phase in an aqueous environment. Other scaffolding proteins could co-assemble into this condensate, but were not necessary for its formation. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
419
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(486 citation statements)
references
References 38 publications
15
419
2
Order By: Relevance
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig. 1B-D).…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 58%
“…Previous studies suggested that the IDLs of adjacent SSB molecules can interact with each other to enhance the cooperativity of ssDNA binding, while the IDL was also proposed to interact with the OB fold Kozlov et al, 2015Kozlov et al, , 2017. Moreover, the central role played by similar low-sequence-complexity, Gln/Gly/Pro-rich IDRs in previously investigated LLPS systems (Bakthavachalu et al, 2018;Mannen et al, 2016;Milovanovic et al, 2018;Sabari et al, 2018) as well as the predicted LLPS propensities suggest a role for the IDL in SSB LLPS ( Fig. 1B-D).…”
Section: Multivalent Interactions Between Ssb Idl Regions Are Requirementioning
confidence: 58%
“…During prolonged stimulation, when the SV recycling process becomes rate limiting, SVs are mobilized from these clusters to ensure reliable SV availability. It was recently proposed that SVs form clusters by phase separation; specifically, the SV peripheral phosphoprotein synapsin‐1 was shown to be able to organize SVs in clusters by liquid–liquid phase separation . Synapsin is an abundant protein and can reversibly associate with SVs .…”
Section: Coordination Between Vesicle Acidification and Trafficking Amentioning
confidence: 99%
“…It was recently proposed that SVs form clusters by phase separation; specifically, the SV peripheral phosphoprotein synapsin-1 was shown to be able to organize SVs in clusters by liquid-liquid phase separation. 74 Synapsin is an abundant protein and can reversibly F I G U R E 3 Hypothetical model of vATPase recycling within the SV recycling pathway. Endocytic retrieval from the plasma membrane by clathrin-dependent mechanism results in the formation of clathrin-coated vesicles, which contain a fully assembled vATPase complex.…”
Section: Coordination Between Vesicle Acidification and Traffickingmentioning
confidence: 99%
“…Moreover, condensates control where reactions occur by clustering molecules or membrane‐bound organelles in specific locations. The clustering of synaptic vesicles and neurotransmitter receptors at presynaptic and postsynaptic regions is mediated by the phase separation of proteins such as Synapsin in the presynapse and SynGAP and PSD‐95 in the postsynapse . Synaptonemal complex condensates control the spatial patterning of meiotic recombination factors …”
Section: Biomolecular Condensates: Assembly Function and Regulationmentioning
confidence: 99%